Enzymatic Cascades for Tailored (13)C(6) and (15)N Enriched Human Milk Oligosaccharides - Fischöder, Thomas (Molecules, 2019)
Several health benefits, associated with human milk oligosaccharides (HMOS), have been revealed in the last decades. Further progress, however, requires not only the establishment of a simple “routine” method for absolute quantification of complex HMOS mixtures but also the development of novel synthesis strategies to improve access to tailored HMOS. Here, we introduce a combination of salvage-like nucleotide sugar-producing enzyme cascades with Leloir-glycosyltransferases in a sequential pattern for the convenient tailoring of stable isotope-labeled HMOS. We demonstrate the assembly of [(13)C(6)]galactose into lacto-N- and lacto-N-neo-type HMOS structures up to octaoses. Further, we present the enzymatic production of UDP-[(15)N]GlcNAc and its application for the enzymatic synthesis of [(13)C(6)/(15)N]lacto-N-neo-tetraose for the first time. An exemplary application was selected—analysis of tetraose in complex biological mixtures—to show the potential of tailored stable isotope reference standards for the mass spectrometry-based quantification, using matrix-assisted laser desorption/ionization-time of flight mass spectrometry (MALDI-TOF-MS) as a fast and straightforward method for absolute quantification of HMOS. Together with the newly available well-defined tailored isotopic HMOS, this can make a crucial contribution to prospective research aiming for a more profound understanding of HMOS structure-function relations.